ANALISIS AKTIVITAS CSR PADA PT. BRI LIFE DALAM MEMPERTAHANKAN CITRA POSITIF" (STUDI PT. BRI LIFE DALAM MEMBANTU GERAKAN MELAWAN COVID-19 DI INDONESIA). - Wahyu Meydhika Paramudyatama (2022)
This study aims to determine the process and mplementation of the activities carried out by PT. BRI Life Insurance in social activities to help the movement against Covid-19 in Indonesia by providing social assistance in the form of medical equipment, basic necessities, cash and clean water supply assistance to areas affected by drought in the midst of a pandemic. This study uses a qualitative descriptive research method. The theory used in this research is Attribution Theory. The data collected in the study consisted of primary data (interviews, documentation and literature study) and secondary data (literature studies and previous research results). From this research, the researcher sought information from several informants related to the activities carried out by the company. Data analysis techniques used in this research are data collection techniques, data reduction, data presentation conclusions and data verification. The results showed that the Public Relations activities carried out by PT. BRI Life Insurance, namely through social responsibility approach activities, through Corporate Social Responsibility program activities to create a good corporate image in the eyes of the public. It can be seen and concluded that the process of the CSR program in the PT. BRI Life Asuransi this time with the aim of helping the public to be more aware of the importance of health and hygiene in helping to change and improve the daily life patterns that exist in the community during the pandemic, to maintain and enhance the positive image of the company